Analisis Fenomena Degradasi Budaya Gotong Royong - Hanifa, Syakira; Anggraeni Dewi, Dinie; Saeful Hayat, Rizky (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Cooperation is a typical Indonesian culture that has been passed down from generation to generation. However, currently cooperation has experienced cultural degradation, many factors influence it. Therefore, a descriptive analysis was made from the data obtained through literature studies in several scientific articles. The result of the analysis prove that the culture of cooperation has experienced a decline due to globalization, modernization, individualist attitudes, and many other causes. Therefore, it is of course very important to carry out carious efforts that can be made to improve and implement the culture of cooperation as one of Indonesia’s culture identities. For example, by utilizing technology and social media to communicate, organize and facilitate collaboration that will be established by each community